Religions as Complex Systems: Features, Purpose and Structure - Andrei-Razvan Coltea (European Scientific Journal, ESJ, 2020)
Complexity is a paradigm whose relevance is currently expanding beyond the domain of ‘hard’ sciences. Humanities and social sciences could greatly benefit from using it as an antidote to reductionism, and religious studies in particular is a field in great need of defragmentation and a broader theoretical perspective. This paper’s ambitious aim is to propose such a perspective while frequently crossing interdisciplinary borders and, by drawing inspiration from and criticizing the work of evolutionary anthropologist Richard Sosis, to offer an integrative analytical framework for the study of religions as allopoietic complex adaptive systems. Firstly, this paper describes the core features of complex systems (non-linear, autopoietic/allopoietic, entropy reducing, open, adaptive, emergent). Secondly, it identifies religions as abstract complex systems and their basic components as signal/noise distinctions of informational inputs from the environment. More importantly, it posits that they fulfill an entropy reducing function in psychic systems by the emergence of meaning. Lastly, it builds a model of religious systems and identifies six building blocks: rituals, myths, taboos, supernatural agents, authority and afterlife beliefs, following Luhmann in claiming that individuals are not part of the system, but of the environment. Consequently, the cooperative behavior of individuals to form social structures cannot constitute the ultimate output of the system, but only a behavioral effect of the actual one, meaning.